Identificação, validação e anotação funcional de marcadores microssatélites em genótipos de cajueiro anão-precoce (anacardium occidentale var. Nanum) utilizando dados de rna-seq. - Soares, Vitória Virgínia Magalhães (2016)
The cashew tree is a native plant from Brazil with high market value. This contributes to the generation of thousands direct and indirect jobs, especially in the Northeast region, during dry season. Breeding programs have been selecting cashew cultivars that best adapt to semi-arid environment in order to fit it in the increasingly competitive market. The search for microsatellite markers can assist breeding programs regarding to access to genetic diversity of the species. This study aims to identify SSR markers in the cashew tree based on seeds and leaves transcriptome, as well as assess its validation by PCR technique in different commercial genotypes. Using bioinformatics tools, SSRs motifs from types di- tri- tetra- penta- and hexanucleotides were found. Trinucleotide-type motif was the most representative in transcripts both from dwarf cashew CCP 76 and common cashew, ranging from 60 to 65%, respectively. Transcripts from common cashew and dwarf cashew CCP 76 share a total of 298 SSR markers. 29 of these were selected for amplification by PCR, in which 9 showed polymorphism in genotypes tested. The sequences located near to the SSR markers encode proteins, which mostly belong to gene families. It can be concluded that regions containing SSRs markers were found in the transcribed region of nine cashew genotypes, and can be a useful tool in genetic analysis and open up prospects for endogenous role of SSRs in protein function.